1996
DOI: 10.1002/(sici)1098-2361(1996)15:3<279::aid-zoo7>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Indoor husbandry of the panther chameleon Chamaeleo Furcifer pardalis: Effects of dietary vitamins A and D and ultraviolet irradiation on pathology and life‐history traits

Abstract: To assess the importance of diet and light for indoor maintenance, hatchling panther chameleons were reared for 1 year on crickets fed diets that differed in vitamin concentrations and in different light environments. Dietary transfer of vitamins from the cricket diet to the lizards via the crickets was quantified, as was UV irradiance. There was a statistically significant dietary enhancement of growth by both vitamins on males. UV-A irradiation significantly suppressed growth of females. Low vitamin A shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 0 publications
1
59
1
Order By: Relevance
“…It may be that wild insectivores use a combination of retinoids (retinol, retinal, and 3-hydroxyretinal) as well as carotenoids to meet their vitamin A requirements. A better understanding of the retinol, retinal, and 3-hydroxyretinal content of insects and the utilization of the retinoids and carotenoids found in insects as a source of vitamin A in insectivores is important because vitamin A deficiency has been reported in several species of captive insectivores (Ferguson et al, 1996;Hoby et al, 2010;Miller et al, 2001;Pessier et al, 2005).…”
Section: Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that wild insectivores use a combination of retinoids (retinol, retinal, and 3-hydroxyretinal) as well as carotenoids to meet their vitamin A requirements. A better understanding of the retinol, retinal, and 3-hydroxyretinal content of insects and the utilization of the retinoids and carotenoids found in insects as a source of vitamin A in insectivores is important because vitamin A deficiency has been reported in several species of captive insectivores (Ferguson et al, 1996;Hoby et al, 2010;Miller et al, 2001;Pessier et al, 2005).…”
Section: Vitamin Amentioning
confidence: 99%
“…Further studies on the vitamin D content of both captive-raised and wild-caught insects should be conducted to provide a better understanding of insect vitamin D content. However, it seems likely that exposure to ultraviolet light is an appropriate way to ensure an adequate vitamin D status in most insectivores (Ferguson et al, 1996;Oonincx et al, 2010).…”
Section: Vitamin Dmentioning
confidence: 99%
“…If chameleons depend on endogenous vitamin D synthesis, exposure to UVB light could be a limiting factor, because many captive chameleons are kept in temperate climates or indoors. It has been previously shown that artificial UVB exposure of panther chameleons (Furcifer pardalis) enhanced hatching success, vitamin D status of adult females, and epidermal vitamin D production (11)(12)(13). In contrast, it has been stated that adequate nutritional provision of cholecalciferol without added UVB light was sufficient to keep and breed veiled chameleons successfully (14).…”
Section: Introductionmentioning
confidence: 99%
“…In growing panther chameleons, a connection between NMBD and low dietary vitamin A content, but not between NMBD and variations of vitamin D contents in the diet, was demonstrated (11). In veiled chameleons, symptoms of hypovitaminosis A were similar to those in other reptiles (skin, eye, respiratory, and neurological lesions) but also included bone lesions (15).…”
Section: Introductionmentioning
confidence: 99%
“…14,17 In contrast, some studies 9,15,19,34 have suggested that dietary calcium supplementation may be unnecessary or even detrimental because it may induce metastatic calcinosis and pathological accumulation. In addition, excess vitamin D provided by owners can have toxic effects in reptiles, 35,36 birds, 37 and mammals, [38][39][40] including humans. 41,42 Hematologic variables, including total calcium, ionized calcium, and phosphorus concentrations, generally are used to assess mineral status in reptiles.…”
mentioning
confidence: 99%